Diagnosis of Tuberculosis Using Gastric Aspirates in Pediatric Patients in Haiti. (24th February 2020) - Pierre-Louis, Marvah Hill; Rouzier, Vanessa; Rivera, Vanessa; Systrom, Hannah K; Julma, Pierrot; Jean, Elsie; Francois, Lovely Cassandra; Pape, Jean W; Ocheretina, Oksana; Wright, Peter F
Abstract: Background: We aimed to determine whether the Xpert MTB/RIF (Xpert) assay is a useful adjunct to culture for the rapid diagnosis of tuberculosis (TB) using gastric lavage aspirates (GLAs) in children aged < 5 years. Methods: We reviewed the yield from diagnostic modalities in children suspected of having TB followed at an infectious disease research and treatment center in Port-au-Prince, Haiti, from 2011 to 2016. Results: In 187 children clinically diagnosed with TB, a microbiologic diagnosis could be established in 40 (21%). Cultures, Xpert, and smears were positive in 30 (19%), 28 (17%), and 3 (1.6%) children, respectively. Ten cases that would not have been diagnosed by culture alone were found by the use of the Xpert assay. Collecting 2 GLA samples optimized microbiologic yield. Conclusions: In GLAs, Xpert increased the yield of microbiologically documented cases by 33%. Additionally, the rapidity of diagnosis potentially makes Xpert a valuable adjunct in initiating treatment for TB in children. Smear microscopy has low sensitivity in GLA and did not add to the documented cases. Our findings also highlight the low rate of microbiologic confirmation of clinically diagnosed TB.